CYBER PLANNING, PRIVATE PROPERTY AND ECONOMIC CALCULATION - Espinosa, Víctor I. (REVISTA PROCESOS DE MERCADO, 2022)
Abstract: This article reviews and discusses Professor Maxi Nieto’s observations on some major topics in in the modern theory of socialism. Notably, his interpretation of the argument against the “possibility” of economic calculus without private property rights developed by the new generation of Austrian school authors. It focuses on methodological issues to highlight the theoretical deficiencies of some of the leading ideas defended by Nieto. It also analyzes his proposal of cyber-communism as an alternative to overcome the challenge of economic calculation through the new information and communication technologies. It argues that his analysis is superficial and that the Austrian’ challenge on the impossibility of socialism remains sound. Keywords: economic calculation; markets; planning; socialism. Classification JEL: B53; P21.